Is theological neutrality the final word in interreligious dialogue?. Issue 3 (10th July 2019) - Rambachan, Anantanand
Abstract: This article offers a response to the ELCA Declaration of Interreligious Commitment from a Hindu perspective. It raises important questions, and presses Lutherans on the issue of evangelism.